Geological offsets and age constraints along the northern Dead Sea fault, Syria - Searle, M; Chung, S; Lo, C (2010)
North of the Lebanese restraining bend, the northern Dead Sea fault in Syria cuts Late Miocene- Pliocene intraplate alkali basalts that have 40Ar/39Ar ages ranging between 6.4 ± 0.1 and 3.7 ± 0.1 Ma. Despite a wide (40 m) gouge zone in places, only between 5.3 and 16.8 km of Pliocene-Recent left-lateral offset occurs along the segment south of Mesyef, where up to 1100 m of down-to-the-east throw has been measured using the base Neogene volcanic rocks as a datum horizon. Although theoretically possible, there is no geological evidence for pre-Pliocene movement along the fault in NW Syria. The fault splays into two transtensional faults bounding the Pliocene Al-Ghab depression and cuts basalts dated at 4.0-3.7 Ma. The minor lateral geological offsets and matching of Mesozoic and Tertiary stratigraphy across the fault show that the northern Dead Sea fault is not a plate boundary, but merely an intraplate fault. The kinematics of NW Syria can be related to a dynamically evolving stress field with time from Miocene NW-SE compression to Pliocene-Recent north-south strike-slip faulting, coupled with minor anti-clockwise rotation, initiation of the Dead Sea left-lateral transtensional strike-slip fault and the transtensional Al-Ghab basin. © 2010 Geological Society of London.